Ch - Cheng (New York: McGraw-Hill higher education, 2010)
System requirements: PC with Pentium-class processor, 90 MHz or higher; 88 MB disk space; Windows 95 or later
To accompany textbook "C for engineers and scientists : an interpretive approach / Harry H. Cheng"
FOEAT
Keywords: C (Computer program language)